Injury profiles of Australian football players across five, women's and girls' competition levels - Farley, J. B.; Keogh, J. W. L.; Woods, C. T.; Milne, N. (Journal of Science and Medicine in Sport, 2022)
Objectives: To describe injury profiles of Australian football players and explore trends across five, women's and girls' competition levels. Design: Prospective cohort study. Methods: Injuries were prospectively recorded by team personnel across one or two seasons of Australian football (2017-18 and/or 2018-19) including five, women's and girls' competition levels (elite senior, non-elite senior, high-level junior, non-elite junior (14-17 years), and non-elite junior (10-13 years)). Injury incidence rates were calculated per 1000 h and injury prevalence calculated for pre-season, early-season, mid-season, and late-season. Descriptive statistics present injury profiles according to activity, body region, pathology, mechanism, and severity. Results: From the 392 included players, 760 injuries were recorded. Overall injury incidence was 20.9 injuries per 1000 h. Injury prevalence was highest during pre-season (64.1%). Most injuries were to the lower extremity (n = 440; 58.0%). Ligament/joint sprain injuries were common (n = 147, 19.3%). Several injuries resulted from contact mechanisms (n = 314, 61.4%), with many due to contact with another player (n = 131, 52.8%). Injuries resulting in time lost from participation were common (n = 444, 58.9%). Competition level injury trends were observed, with elite senior (125.1 injuries per 1000 h) and high-level junior (116.9 injuries per 1000 h) players having greater match injury incidence compared to their non-elite counterparts (15.5-41.4 injuries per 1000 h). Conclusions: This study provides preliminary insight into injury profiles of Australian football players in women's and girls' competitions. These findings can drive future injury risk reduction research specific to this population across the developmental pathway.